Dynamic Capabilities for the Development of Innovation Capability - Froehlich, Cristiane; Bitencourt, Claudia Cristina (Revista de Administração da UFSM, 2019)
The present article aims at analyzing the dynamic capabilities’ contributions for the development of innovation capability in a chemical sector company. The company headquarters are located in the state of Rio Grande do Sul, Brazil, with branches in other states in Brazil, Latin America and China. More specifically, it concerns the company’s innovation strategies and practices related to sensing, seizing and reconfiguration capabilities and their micro-foundations, as presented by Teece (2007). This research is classified as a descriptive and qualitative case study. Data were collected through 10 semi-structured interviews and analyzed through the qualitative content analysis. The main results show that the dynamic capabilities help to develop innovation capability. This research checked that the approach on dynamic capabilities is of fundamental importance for the development of innovation capability by reinforcing it as an organizational strategy.